Quantitative proteomics analysis reveals an important role of the transcriptional regulator UidR in the bacterial biofilm formation of Aeromonas hydrophila - Li, Xiaoyan; Tian, Feng; Zhang, Binghui; Zhang, Lishan; Chen, Xiaomeng; Lin, Xiaoke; Wang, Yuqian; Lin, Xiangmin; Liu, Yanling (Frontiers in Cellular and Infection Microbiology, 2024)
Bacterial biofilm is a well-known characteristic that plays important roles in diverse physiological functions, whereas the current intrinsic regulatory mechanism of its formation is still largely unknown. In the present study, the deletion of gene uidR encoding a TetR transcriptional regulator significantly increased the biofilm formation in Aeromonas hydrophila. To further understand its role in biofilm formation, a labelfree based quantitative proteomics technology was conducted to compare the differentially expressed proteins (DEPs) between ΔuidR and the wild-type strain in the biofilm state. The results showed that there was a total of 220 DEPs, including 120 upregulated proteins and 100 down-regulated proteins. Bioinformatics analysis suggested that uidR may affect bacterial biofilm formation by regulating some related proteins in glyoxylic acid and dicarboxylic acid pathway. The expressions of selected proteins involved in this pathway were further confirmed by q-PCR assay, and the results was in accordance with the quantitative proteomics data. Moreover, the deletion of four genes (AHA_3063, AHA_3062, AHA_4140 and aceB) related to the glyoxylic acid and dicarboxylic acid pathway lead to a significant decrease in the biofilm formation. Thus, the results indicated that uidR involved in the regulatory of bacterial biofilm formation, and it may provide a potential target for the drug development and a new clue for the prevention of pathogenic A. hydrophila in the future.